Comparative study of hypoglycaemia induced by opioids. Is it a class effect? - Chrétien, Basile; Dolladille, Charles; Hamel-Senecal, Léa; Sassier, Marion; Faillie, Jean Luc; Miremont‐Salamé, Ghada; Lelong‐Boulouard, Véronique; Boisselier, Reynald Le; Fédrizzi, Sophie; Alexandre, Joachim; Humbert, Xavier (Expert Opinion on Drug Safety, 2019)
Objective: Drug-induced hypoglycaemia has been described with the use of tramadol and methadone. The authors aimed to determine if drug-induced hypoglycaemia could be a class effect for opioids.Methods: The authors performed a disproportionality analysis in VigiBase®, the WHO global individual case safety report database with nine opioids (codeine, fentanyl, hydromorphone, methadone, morphine, oxycodone, tramadol, buprenorphine and nalbuphine) using the broad Standardised MedDRA Query for hypoglycaemia. The authors also carried out a descriptive study of opioid-induced hypoglycaemia in the French PharmacoVigilance DataBase (FPVDB) using the MedDRA Preferred Term ‘hypoglycaemia’.Results: The global adjusted Reporting Odds Ratio (aROR) value for the 9 opioids was 1.53 (95% CI 1.52–1.54). The aROR ranged from 1.09 to 1.97 depending on the opioid, but all were statistically significant. A sex ratio of 0.74 was found for the reports of opioid-induced hypoglycaemia in Vigibase®. The authors also found 133 reports of hypoglycaemia in the FPVDB related to opioids. Among the reports, 55 were glycaemic imbalances in diabetics occurring shortly after the start of opioid treatment.Conclusion: This work highlighted a significant association between all opioids and hypoglycaemia, thereby indicating that opioid-induced hypoglycaemia is probably a class effect. Women and/or diabetics seem to be more at risk for developing opioid-induced hypoglycaemia.